Outpatient Antibiotic Prescribing Among United States Nurse Practitioners and Physician Assistants. (10th August 2016) - Sanchez, Guillermo V.; Hersh, Adam L.; Shapiro, Daniel J.; Cawley, James F.; Hicks, Lauri A.
Abstract: We examined US nurse practitioner (NP) and physician assistant (PA) outpatient antibiotic prescribing. Antibiotics were more frequently prescribed during visits involving NP/PA visits compared with physician-only visits, including overall visits (17% vs 12%, P < .0001) and acute respiratory infection visits (61% vs 54%, P < .001). Antibiotic stewardship interventions should target NPs and PAs.